An approach for building Mobile Web Applications through Web Augmentatio - Bosetti, Gabriela Alejandra (2017)
Mobile Web Applications combine traditional navigation access enriched with location-based services, which results in a more complex development process since there are a myriad of issues to consider while integrating these kinds of behaviours. This complexity increases even more if the integration of another specific functionality is considered, as personalization or context-aware services. In this article we present a novel approach to facilitate the development of Web applications that enhance existing ones with mobile features through client-side Web Augmentation. Assuming the existence of a set of Web pages that could be associated to a physical object and some mechanism for location sensing, we allow developers to define mobile services or adaptations according to their own interests. We present a detailed comparative analysis of the features we provide against other similar approaches, in order to clearly highlight those aspects that distinguish our work from the existing ones. Finally, we show that this approach is feasible and effective by presenting two prototype applications for two possible scenarios and the results of our first experiment.